Androids build your own lifelike robots - Bergeron, Bryan P.; Talbot, Thomas B. (McGraw-Hill Education, 2014)
Annotation Create the next generation of AUTONOMOUS ANDROIDSConstruct self-governing 'droids that display physiologically correct behaviors. Co-written by experts in the fields of robotics, artificial intelligence, and medicine, "Androids: Build Your Own Lifelike Robots" features low-cost DIY projects that translate human physiology into cybernetics. Teach your creations to maneuver with an arsenal of behaviors, respond to stimuli, talk, and listen. This practical, inventive guide even shows how to realistically simulate emotion and aging in your robots. Understand cybernetic and robotics principles Work with programmable microcontrollers Choose and wire sensors, actuators, and servos Program dazzling reflex arcs and behavior loops Enable your automatons to speak and hear Build beating hearts and limbs with flowing veins Create breathing patterns that respond to triggers Mimic humanoid feelings and facial expressions Use prototyping kits and testing devices.